If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (2 + x) = 66 Remove parenthesis around (2 + x) 3x + 2 + x = 66 Reorder the terms: 2 + 3x + x = 66 Combine like terms: 3x + x = 4x 2 + 4x = 66 Solving 2 + 4x = 66 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 4x = 66 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = 66 + -2 4x = 66 + -2 Combine like terms: 66 + -2 = 64 4x = 64 Divide each side by '4'. x = 16 Simplifying x = 16
| 3(9)-0.5y=5 | | -15m-2=28 | | 118+-5x=-7x+130 | | 7.8y+2=165 | | 13a+-8b=c | | 7x-5x-(8x+6)= | | 8+2y+2x=0 | | 14+m=n | | 6x-(5x+1)= | | 59x-(39x-78)= | | 15x+20y=360 | | 25(2x-3)=125 | | 13x+7=6x+7 | | 2*x-2=22 | | t+.08t=37 | | 6(13+4)= | | 3x+7=-3x+2+2+6x | | 5x^2+4x+1=225 | | 73=2x+7(x-5) | | 6(3.2m-1)=3.6 | | y=-3*1-4 | | (-4x-2)+(13x+1)= | | .111y-4=-9 | | y+8=12(x-6) | | 4*6+x=24 | | 50+75=359 | | 80x+2x=1000 | | (6x-7)(6x-7)=0 | | -2x+15=18 | | -28+s=15 | | 5*2x-1=45 | | -(5x-2y+7z)= |